2019
DOI: 10.30621/jbachs.2019.745
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Piceatannol, a Resveratrol Metabolite, on Staphylococcus Aureus

Abstract: Objectives: Staphylococcus aureus (S. aureus) is one of the major human pathogens in both community acquired and nosocomial infections. Heavy increase of antibiotic resistance between S. aureus strains became an important public health problem in progress of time. In this study, the antimicrobial effects of piceatannol on S. aureus growth was investigated. Patients and Methods: The antimicrobial effect of piceatannol on a standard S. aureus (DSMZ 6148) strain and two clinical S. aureus strains (C1 and C2) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Among them, J-28 was a multidrug-resistant bacterium. In addition, we determined the MIC of PIC against S. aureus to be 64∼128 µg/mL, which is different from that of a previous study [21]. In analyzing the results of the MIC and MBC, we found no difference in the antibacterial activity of PIC against drug-resistant and sensitive bacteria.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Among them, J-28 was a multidrug-resistant bacterium. In addition, we determined the MIC of PIC against S. aureus to be 64∼128 µg/mL, which is different from that of a previous study [21]. In analyzing the results of the MIC and MBC, we found no difference in the antibacterial activity of PIC against drug-resistant and sensitive bacteria.…”
Section: Discussioncontrasting
confidence: 86%
“…Moreover, PIC also exhibits anti-inflammatory, anti-adipogenesis, and anti-melanin production activities [ 19 ]. Most importantly, PIC can inhibit the biofilm of Streptococcus mutants and exhibits antibacterial activity against S. aureus [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guldas et al demonstrated the antimicrobial effect of PIC on standard strains of S. aureus and two clinical strains of S. aureus (C1 and C2), tested in vitro at different concentrations between 0 and 750 μg/mL. 64 The findings of the in vitro study exhibited that after 24 and 48 h of PIC treatment, the average minimum inhibitory concentrations (MIC) for all strains tested were 283 and 383 μg/mL, as well as the average minimum bactericidal concentrations, which were 717 and 583 μg/mL. Inhibition of S. mutans biofilm via inhibition of glucosyltransferase (Gtfs) using PIC was described by Nizampatanam et al 65 It was observed that PIC exhibited low micromolar antibiofilm activity with a selectivity index of around 11 by inhibiting Gtfs, a major virulence factor in S. mutans.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…From the animal study, it was observed that PIC significantly reduces the formation of bacterial colonies and inflammatory responses in target organs. Guldas et al demonstrated the antimicrobial effect of PIC on standard strains of S. aureus and two clinical strains of S. aureus (C1 and C2), tested in vitro at different concentrations between 0 and 750 μg/mL 64 . The findings of the in vitro study exhibited that after 24 and 48 h of PIC treatment, the average minimum inhibitory concentrations (MIC) for all strains tested were 283 and 383 μg/mL, as well as the average minimum bactericidal concentrations, which were 717 and 583 μg/mL.…”
Section: Activity Of Piceatannol On Various Diseasesmentioning
confidence: 99%